Effect of Energy-Protein Ratio on the Performance of Laying Chickens in the Northern Guinea Savanna Zone of Nigeria - Yusuf, H. B.; Yahaya, M. S.; Yakubu, B.; Duwa, H. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
The aim of this study was to investigate the effect of energy-protein ratio on the performance of laying chickens in the northern guinea savanna zone of Nigeria. Two hundred and forty three (243) point of lay pullets (Isa Brown), were randomly allocated to nine treatments, replicated three times in a 3×3 factorial design. The chickens were fed 9 treatment diets containing 3 energy (2500, 2700 and 2900ME (kcal/kg) and 3 crude protein (CP) levels (16, 17 and 18%) respectively. Feed and water were given ad-libitum. Parameters measured include feed intake, body weight, body weight gain, feed conversion ratio, egg production, egg weight, mortality and cost benefit analysis. Laying chickens fed high protein diets (18% CP), recorded the highest feed intake (743.63g/bird/week), feed conversion ratio (13.48), number of eggs produced (5.12/bird/week) and lowest body weight gain (62.48g) and egg weight (53.47g) while those fed low protein diets (16% CP) recorded the highest body weight gain (292.47g), lowest feed intake (597.33g/bird/week), feed conversion ratio (2.43), number of eggs produced (4.19/bird/week) and egg weight (54.11g). Layers fed medium protein diet (17% CP) recorded the highest egg weight (55.22g). The study showed that laying chickens fed low (2500 kcal ME/kg), medium (2700 kcal ME/kg) and high (2900 kcal ME/kg) energy with high protein (18% CP) produced significantly more eggs than those on low (16% CP) or medium (17% CP) proteins. Based on the study, it was concluded that laying chickens perform better on 2500 ME (kcal/kg) diet at 17% CP at lower feed costs. It is therefore recommended that laying chickens should be fed 2500 ME (kcal/kg) diet at 17% CP.